Digital economy in Russia - Khusnutdinova, G. F.; Khamathanova, M. A. (International Journal of Psychosocial Rehabilitation, 2020)
The authors consider the trends and prospects for the development of the digital economy in this article. The authors study the terminology of the "digital economy", its specifics and content. Statistical data reflecting the peculiarities of the digital economy implementation in Russia are presented. The authors also explore positive trends in the development of the digital economy.